Strongyloides stercoralis hyperinfection in a patient with rheumatoid arthritis and bronchial asthma: a case report - Yildiz Levent; Bektas Ahmet; Hokelek Murat; Cakar Burcu; Altintop Levent; Karaoglanoglu Muge (BMC, 2010)
Abstract Objective Strongyloides stercoralis is a soil-transmitted intestinal nematode that has been estimated to infect at least 60 million people, especially in tropical and subtropical regions. Strongyloides infection has been described in immunosupressed patients with lymphoma, rheumatoid arthritis, diabetes mellitus etc. Our case who has rheumatoid arthritis (RA) and bronchial asthma was treated with low dose steroids and methotrexate. Methods A 68 year old woman has bronchial asthma for 55 years and also diagnosed RA 7 years ago. She received immunusupressive agents including methotrexate and steroids. On admission at hospital, she was on deflazacort 5 mg/day and methotrexate 15 mg/week. On her physical examination, she was afebrile, had rhonchi and mild epigastric tenderness. She had joint deformities at metacarpophalengeal joints and phalanges but no active arthritis finding. Results Oesophagogastroduodenoscopy was performed and it showed hemorrhagic focus at bulbus. Gastric biopsy obtained and showed evidence of S.Stercoralis infection. Stool and sputum parasitological examinations were also all positive for S.stercoralis larvae. Chest radiography result had no pathologic finding. Albendazole 400 mg/day was started for 23 days. After the ivermectin was retrieved, patient was treated with oral ivermectin 200 μg once a day for 3 days. On her outpatient control at 15th day, stool and sputum samples were all negative for parasites. Conclusion S.stercoralis may cause mortal diseases in patients. Immunosupression frequently causes disseminated infections. Many infected patients are completely asymptomatic. Although it is important to detect latent S. stercoralis infections before administering chemotherapy or before the onset of immunosuppression in patients at risk, a specific and sensitive diagnostic test is lacking. In immunosupressed patients, to detect S.stercoralis might help to have the patient survived and constitute the exact therapy.